1984
DOI: 10.1099/0022-1317-65-1-55
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Transport of Herpes Simplex Virus in Neurites of Rat Dorsal Root Ganglia Cells in Culture

Abstract: SUMMARYAttachment and neuritic transport of herpes simplex virus (HSV) type 1 (McIntyre) were studied in a cell culture system with dissociated cells of rat dorsal root ganglia. The two-chamber cell culture system containing a diffusion barrier penetrated by neurites of cultured sensory neurons permitted infection of neurites extending outside the diffusion barrier without exposure of the neuronal cell soma. HSV adsorbed to neuritic extensions and reached the neuronal soma within 1.5 h post-inoculation. Neurit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
92
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(102 citation statements)
references
References 18 publications
10
92
0
Order By: Relevance
“…Within neurons, HSV-1 nucleocapsid and tegument proteins travel in a retrograde manner to the neuronal cell body where the viral genome is released into the nucleus. [96][97][98] The transport of alphaherpesvirus nucleocapsids along axons has been estimated to occur at rates of 0.5-3.5 mm/s, 99 suggesting that transport is an active process. While the exact mechanism of HSV transport along axons has yet to be elucidated, recent studies have identified viral and host cell components that contribute to this process.…”
Section: Virus Attachment and Entrymentioning
confidence: 99%
“…Within neurons, HSV-1 nucleocapsid and tegument proteins travel in a retrograde manner to the neuronal cell body where the viral genome is released into the nucleus. [96][97][98] The transport of alphaherpesvirus nucleocapsids along axons has been estimated to occur at rates of 0.5-3.5 mm/s, 99 suggesting that transport is an active process. While the exact mechanism of HSV transport along axons has yet to be elucidated, recent studies have identified viral and host cell components that contribute to this process.…”
Section: Virus Attachment and Entrymentioning
confidence: 99%
“…HSV is thought to travel retrogradely toward the cell nucleus in the absence of a viral envelope or a cell-derived membrane compartment (Lycke et al, 1984(Lycke et al, , 1988Marchand and Schwab, 1986). Although HSV has not yet been evaluated in in vitro mobility assays, these data suggest that the virus is transported on axonal microtubules in a manner similar to the translocation of fluorescent microspheres, microinjected beads, paraffin droplets, or glass fragments (Adams and Bray, 1983;Colin et al, 1989).…”
Section: Autoradrographymentioning
confidence: 99%
“…DRG ceils were obtained by dissecting 10 to 12 Wistar rat embryos (at day 15 to 17) as described in earlier reports (Lycke et al, 1984;Lycke & Tsiang, 1987). Ganglia were collected using forceps under a dissection microscope and cells were dissociated by treatment with 0.25 % trypsin in Ca 2+-and Mg2+-free Hanks' buffer at pH 7.2 for 30 min at 37 °C.…”
Section: Virusmentioning
confidence: 99%
“…Whereas conventional neuronal cultures are less appropriate for the investigation of viral transport, neurons cultivated in a compartmentalized culture system as described by Campenot (1977) will demonstrate convincingly the transport of herpes simplex virus in vitro (Kristensson et al, 1986;Lycke et al, 1984;Ziegler & Herman, 1980) and the retrograde transport of both fixed and street rabies viruses in cultured rat sensory neurons (Lycke & Tsiang, 1987;Tsiang, 1988). In this system, herpes and rabies viruses were transported in a retrograde fashion with a velocity in the range of 50 mm/day (herpes virus) and 25 mm/day (rabies virus) (Lycke et al, 1984;Lycke & Tsiang, 1987).…”
Section: Introductionmentioning
confidence: 99%